Analisis Wilayah Jelajah dan Kondisi Habitat Monyet Ekor Panjang (Macaca fascicularis) di Taman Nasional Kelimutu (Studi Kasus Zona Pemanfaatan Taman Nasional Kelimutu, Kabupaten Ende, Provinsi Nusa Tenggara Timur) - Azahra Rahmadani; Maria M. E. Purnama; Norman P. L. B. Riwu Kaho; Fadlan Pramatana (Wana Lestari, 2025)
This research was conducted to determine the range and core area of ​​the Long-tailed Macaque (Macaca fascicularis). This research was carried out in the Kelimutu National Park, specifically the Utilization Zone of the Kelimutu National Park, Ende Regency, East Nusa Tenggara which was conducted for 1 month, from November to December 2022. This research used the Zoatrack WebGIS method which organizes home ranges using the Minimum Convex Polygon (MCP). and core areas using Kernel Utilization Distribution and data analysis using descriptive analysis. The results showed that the home range area analyzed using the Minimum Convex Polygon (MCP) was 47.7 Ha, with the home range of the Long-tailed Monkey (Macaca fascicularis) located in almost the Utilization Zone of Kelimutu National Park. The results of the analysis of the core area using the Kernel Utilization Distribution show that the area of ​​the core area is 16.2 Ha. The results of the core area show that there are two core areas that are frequently visited by the Long-tailed Macaque (Macaca fascicularis), this is due to the large number of visitors who are a source of food and trees as a place to rest in the Kelimutu National Park area.